UZBEKISTAN'S QUALIFICATION FOR THE FIFA WORLD CUP: A HISTORICAL AND SYSTEMIC ANALYSIS (Ustozlar uchun, 2026)
The Uzbekistan national football team has officially secured qualification for the FIFA World Cup for the first time in its history. This marks an unprecedented achievement, not only for the country but for the entire Central Asian region, as no other nation from this area has previously reached this global stage. The qualification is a direct result of systematic planning, internal discipline, and long-term resilience.The foundation for international expectations was laid in 1994 when the national team won gold medals at the Asian Games in Hiroshima. Following this early success, however, the team faced multiple structural and tactical setbacks during successive World Cup qualification campaigns. Notable historical challenges included controversial refereeing decisions during the 2006 qualifiers, elimination based on goal difference in 2014, and critical tactical failures in the final seconds of the 2018 qualifiers.